Proyecto Tesauro de Cine Español - Bechini i Tristany, Mònica; Burguillos Martínez, Ferran; Calle Buendía, Josep; Díaz Mota, Albert; Gutiérrez Robles, Vanessa (Cuadernos de Documentación Multimedia, 2018)
Proyecto Tesauro de Cine Español